The Role of Extension Officers in Increasing Business Success (Case study on Lintas Harapan livestock business group) - Pratama, Bimma; Solfema, Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the role of extension workers in increasing business success. The aim is to find out how the role of extension workers is in educating members so that later they will achieve better results so that later they can improve the economy and the community's knowledge in raising livestock. improve skills and increase community knowledge. The purpose of this study was to see the role of extension workers in the learning process in the cross-expectation livestock business group. research is based on a qualitative approach with case study research. Data sources in this case are extension workers, chairmen, secretaries, treasurers, and members of the Cross-Hope Livestock Business Group. Data collection techniques used in this study were observations, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing.  Data validation technique uses triangulation. Research result shows that the role of extension workers here is as a facilitator, innovator, and motivator. With this group of women farmers, the community should be aware that we need to take advantage of our yards by planting something that is healthy and able to help with household needs and increase family income.